The turnaround of literature and thinking in the XXth century: Interventions of the Reception Aesthetics and Deconstruction - Maria Antonieta Jordão de Oliveira Borba (Gragoatá, 2016)
Introduction of the main aspects of the ideas of Hans Robert Jauss, Wolfgang Iser, Michel Foucault and Jacques Derrida, as some of the most important proposals of the epistemological rupture carried out by two major lines of the XXth century, respectively the Reception Aesthetics and French Deconstruction. Development of the modes whereby each of these notions occurred in such lines in the 70s, to disrupt the metaphysical conceptions on Literature and Western Philosophy.